Advances in gravity concentration - Honaker, R. Q. 1963-; Forrest, W. R. 1961- (Society for Mining, Metallurgy, and Exploration, 2003)
This compilation focuses on state-of-the-art developments and future trends in gravity concentration technologies. Leading experts discuss recent developments in the design, optimization, and control of gravity-based separation processes and their associated applications. The book is divided into three sections: fundamentals, coal applications, and non-coal applications. The fundamentals section reviews developments in the knowledge of particle characterization, particle-setting kinetics, slurry rheology, and overall process modeling. Papers examine novel technological and circuitry advances i.